Temperature Dependence Study of Mesa-Type InGaAs/InAlAs Avalanche Photodiode Characteristics. (12th January 2017) - Huang, Jack Jia-Sheng; Chang, H. S.; Jan, Yu-Heng; Ni, C. J.; Chen, H. S.; Chou, Emin
Abstract : Avalanche photodiodes (APDs) are key optical receivers due to their performance advantages of high speed, high sensitivity, and low noise. The most critical device parameters of APD include the avalanche breakdown voltage and dark current. In this work, we study the temperature dependence of the breakdown voltage and dark current of the mesa-type APD over a wide temperature range of 20–145°C. We institute an empirical model based on impact ionization processes to account for the experimental data. It is shown that highly stable breakdown characteristics of mesa-type APD can be attained with the optimization of the multiplication layer design. We have achieved excellent stability of avalanche breakdown voltage with a temperature coefficient of 0.017 V/°C. The temperature dependence of dark current is attributed to generation-recombination mechanism. The bandgap energy is estimated to be about 0.71 eV based on the temperature variation of dark current, in good agreement with the value for InGaAs.